2019
DOI: 10.21521/mw.6215
|View full text |Cite
|
Sign up to set email alerts
|

Degree of deformity and certain hormone, vitamin and trace element levels in the serum of calves with congenital flexural deformity

Abstract: The present study aimed to investigate the correlation between certain hormone, vitamin and trace element levels and congenital defects in calves with congenital flexural deformity. The study included 15 calves (study group) which were clinically and radiologically diagnosed with congenital flexural deformity and 15 clinically healthy calves (control group). After obtaining the anamnesis of the calves, general physical, clinical and radiological examinations of the extremities were conducted. The calves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
(23 reference statements)
3
2
0
Order By: Relevance
“…This was dissimilar to the previous report of Ochube et al [ 20 ], who stated that the knee joint was more prone to develop deformity than the fetlock joint. Fazili et al [ 8 ] reported forelimb knuckling at a higher prevalence, similar to our finding. We have recorded all the cases in the front leg.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This was dissimilar to the previous report of Ochube et al [ 20 ], who stated that the knee joint was more prone to develop deformity than the fetlock joint. Fazili et al [ 8 ] reported forelimb knuckling at a higher prevalence, similar to our finding. We have recorded all the cases in the front leg.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the number of male calves with flexural deformity was higher than the females, similar to previous researchers [ 7 , 8 ]. Because male calves gain more weight at birth than female calves, there may be a weight disparity between the fetus and the mother, limiting the fetus’s usual mobility within the uterus and eventually leading to the development of constricted limbs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations